Falls in the workplace (Australia : Safetycare Australia, 2000)
The Concept of Falls - explores the range and scope of falls in the workplace. In many instances people only think about falls from heights but as this program shows there are a large number of ways that people can receive injuries from falls
Title from title screen
VCD format
Keywords: Industrial safety; Falls (Accidents) -- Prevention